THE EFFECT OF THE QUANTUM TEACHING (TANDUR) METHOD ON ARABIC WRITING SKILLS AMONG EIGHTH-GRADE FEMALE STUDENTS AT AN ISLAMIC JUNIOR HIGH SCHOOL / تأثير استخدام طريقة التعليم الكمي بخطوات تاندور على مهارة الكتابة لدى طالبات الفصل الثامن بالمدرسة المتوسطة السلفية الشافعية سبلاك جومبانج - Hikmah Nur Hidayah; Restu Budiansyah Rizki (Universitas Islam Negeri Palopo, 2026)
This study was motivated by the low Arabic writing skills of eighth-grade students at the Islamic junior high school level. In the learning process, many students still experienced difficulties in writing Arabic vocabulary and arranging sentences correctly. In addition, the lack of variation in teaching methods made students less active and less motivated in learning Arabic, especially in writing skills. Therefore, an effective teaching method was needed to create an active, enjoyable, and interactive learning atmosphere. This research aimed to determine the implementation of the Quantum Teaching method, the students’ writing skills, and the effect of the Quantum Teaching method through the “TANDUR” stages on students’ Arabic writing skills. This study used a quantitative approach with an experimental method through a One Group Pre-test and Post-test Design. The sample consisted of 20 eighth-grade students of Madrasah Tsanawiyah. Data were collected through observation, interviews, documentation, and tests, then analyzed using the Paired Sample t-Test. The results showed that the implementation of the Quantum Teaching method was carried out well and created an active and enjoyable learning atmosphere. Students’ writing skills improved after the treatment. The statistical analysis showed that the significance value was 0.000 < 0.05, indicating that the alternative hypothesis was accepted. Thus, the Quantum Teaching method had a significant effect on students’ Arabic writing skills.